Ict-Based Instructional : Microsite-Based Learning For Accounting Students In Sekolah Harapan Utama - Agung Wibowo (Universitas Internasional Batam, 2023)
The problem that is usually faced by teachers related to the preparation of teaching materials is that the teacher gives too much material or teaching materials and sometimes even too little explanation of the material being taught. The facility of ICT that covers internet access and technological tools availability becomes the main problem teachers have in the ICT integration. This research resulted in the creation of site-based learning materials for independent learning media. This output is intended to be used as evaluation material in order to make resolution steps related to the author's problems encountered during the implementation process. The authors performed three methods of data collection techniques. The author carried out this method using quantitative methods. This method the authors use to overcome obstacles based on the findings. The findings show that the integration of vocational and high school learning in English subjects is not suitable for integration considering that their scientific studies are different. Therefore self-learning based learning using ICT is suitable for application.